Analysis of Complete Chloroplast Genome Sequences Improves Phylogenetic Resolution in Paris (Melanthiaceae) - Huang, Yuling; Li, Xiaojuan; Yang, Zhenyan; Yang, Chengjin; Yang, Junbo; Ji, Yunheng (Frontiers in Plant Science, 2016)
The genus Paris in the broad concept is an economically important group in the monocotyledonous family Melanthiaceae (tribe Parideae). The phylogeny of Paris was controversial in previous morphology-based classification and molecular phylogeny. Here, the complete cp genomes of eleven Paris taxa were sequenced, to better understand the evolutionary relationships among these plants and the mutation patterns in their chloroplast (cp) genomes. Comparative analyses indicated that the overall cp genome structure among the Paris taxa is quite similar. The triplication of trnI-CAU was found only in the cp genomes of P. quadrifolia and P. verticillata. Phylogenetic analyses based on the complete cp genomes did not resolve Paris as a monophyletic group, instead providing evidence supporting division of the twelve taxa into two segregate genera: Paris sensu strict and Daiswa. The sister relationship between Daiswa and Trillium was well supported. We recovered two fully supported lineages with divergent distribution in Daiswa; however, none of the previously recognized sections in Daiswa was resolved as monophyletic using plastome data, suggesting that the infrageneric relationships and biogeography of Daiswa species require further investigation. Ten highly divergent DNA regions, suitable for species identification, were detected among the twelve cp genomes. This study is the first successful attempt to provide well-supported evolutionary relationships in Paris based on phylogenomic analyses. The findings highlight the potential of the whole cp genomes for improving resolution in phylogeny as well as species identification in phylogenetically and taxonomically difficult plant genera.